Performance Comparison of Automated Website GUI Testing Tools: A Study of Selenium IDE, Katalon Studio, UI.Vision, and BugBug - Rozi, Muhammad Javier Dafa; Sulistiyani, Endang; Budiarti, Rizqi Putri Nourma (TEKNOLOGI DITERAPKAN DAN JURNAL SAINS KOMPUTER, 2025)
Software testing consumes approximately 50% of development time and cost. One of the most commonly used testing activities is GUI testing, which is still frequently carried out manually. In manual testing, testers often repeat the same actions multiple times, increasing the risk of human error. In contrast, automated testing utilizes specialized tools to minimize these errors. Therefore, selecting the right tool and understanding its performance are crucial. Previous studies on automated testing generally focused only on implementing test objects without evaluating the actual performance quality of the tools used. There are many automated testing tools available that offer capture-and-replay features, such as Selenium, Katalon Studio, UI.Vision, and BugBug. This study compares the performance of these tools for website GUI testing using two parameters: execution time and encountered issues. A total of 21 test cases were designed and executed by the researcher. The execution results show that Katalon Studio, UI.Vision, and BugBug successfully completed all test cases as expected. However, Selenium failed to execute 5 test cases due to its inability to perform hover dropdown actions. In contrast, Katalon Studio, UI.Vision, and BugBug did not encounter issues during execution. In terms of test execution time, Katalon Studio recorded the fastest average time at 6.15 seconds, followed by Selenium. UI.Vision and BugBug required longer execution times, with average times of 20.85 seconds and 22.8 seconds respectively.